Analisis hadis tentang hak dan kewajiban suami isteri - Ramadan, Ahmad (Maliki Interdisciplinary Journal, 2024)
Hadith is the second source for Muslims after the Koran, which is the words of the actions and silences of the Prophet ﷺ. To ensure that a hadith really comes from him, analysis is needed. Which in this case focuses on a hadith narrated by Imam Bukhori in his Shohih Book which talks about the rights of husbands and the obligations of wives. The results of this study state that this Hadith is an authentic hadith so that it is valid and can be disseminated. The content includes 3 things; (1) A wife is punished as a person who disobeys her husband when he is asked to sleep (jimak) but he doesn't want to; (2) It is permissible to curse a Muslim who has sin in terms of simply frightening him; and (3) A wife is obligated to fulfill her husband's wish if she is invited to fulfill it.